2018
DOI: 10.1093/aje/kwy139
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of Respiratory Data From 9 US Population-Based Cohorts

Abstract: Chronic lower respiratory diseases (CLRDs) are the fourth leading cause of death in the United States. To support investigations into CLRD risk determinants and new approaches to primary prevention, we aimed to harmonize and pool respiratory data from US general population-based cohorts. Data were obtained from prospective cohorts that performed prebronchodilator spirometry and were harmonized following 2005 ATS/ERS standards. In cohorts conducting follow-up for noncardiovascular events, CLRD events were defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 68 publications
4
63
0
1
Order By: Relevance
“…This manuscript supports and extends previous and ongoing initiatives on data harmonization (15-21, [43][44][45][46]. Two novel features of our harmonization process are:…”
Section: Reference Definitionssupporting
confidence: 81%
“…This manuscript supports and extends previous and ongoing initiatives on data harmonization (15-21, [43][44][45][46]. Two novel features of our harmonization process are:…”
Section: Reference Definitionssupporting
confidence: 81%
“…Our study used pre-bronchodilator pulmonary function from a broad range of cohorts. We leveraged extensive quality control and harmonization efforts for pulmonary function using standardized criteria 48 , and previously demonstrated that the effect of using pre-vs post-bronchodilator measures has minimal impact on genetic association 49 . Our analysis of cross-sectional data, adjusting for age and smoking exposure, does not specifically address determinants of change in lung function over time or other phenotypes that may be important in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized data from 9 US general populationbased studies that collected spirometry data. 13 The current report is limited to 4 cohorts that completed follow-up for COPDrelated clinical events: the Atherosclerosis Risk in Communities Study (ARIC) 14 ; Cardiovascular Health Study (CHS) 15 ; Health, Aging and Body Composition Study (Health ABC) 16 ; and the Multi-Ethnic Study of Atherosclerosis (MESA). 17 CHS and Health ABC were designed to study older adults, whereas ARIC and MESA included both middle-aged and older adults (eTable 1 in the Supplement).…”
Section: Study Populationmentioning
confidence: 99%
“…21 Lifetime smoking status was classified as never or ever by comparison of self-reported smoking status over all available examinations. 13 Height was measured using standard methods. Due to the extensive quality control and harmonization efforts performed in the NHLBI Pooled Cohorts Study, 13 missing covariate data at enrollment were rare (<1% [eFigure 1 in the Supplement]).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation